1989
DOI: 10.1177/104063878900100204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vitamin K3 Feed Additive for Prevention of Sweet Clover Disease

Abstract: Abstract. Sweet clover poisoning in cattle is caused by an anticoagulant (dicumarol) that is formed in moldy sweet clover hay. Previous experiments with vitamin K 3 and vitamin K 3 in therapy trials indicated that vitamin K 3 was effective in reducing prothrombin times but vitamin K 3 was not. As a possible alternative in the use of toxic sweet clover hays, vitamin K 3 was evaluated to see if it would prevent hemorrhagic crises when fed to cattle consuming toxic sweet clover hay. Vitamin K 3 levels of 0, 0.45,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…At that time, healthy cattle suddenly became dying of internal bleeding and the cause was unknown 11 .Karl Link and his students started the isolation of the active substance from the coumarin that caused the bleeding and found 3,3'methylene-bis-[4-hydroxycoumarin], naturally oxidized coumarin was found in hay fed to livestock 12 . The bleeding disease is also known as -sweet clover disease‖ because livestock eat sweet clover that has been infected with the fungus 13. In research, it was found that natural coumarin is oxidized in moldy hay, to form a substance better known as dicoumarol 13 . The discovery of the bioactive properties of dicoumarol resulted from the investigation of a mysterious livestock disease in the 1940s and later developed as a drug in the 1950s as warfarin 14. Warfarin was first used in 1948 as a rodenticide before the US Food and Drug Administration (FDA) approved it for medical use for anticoagulants in 1954.…”
Section: Overview Of Warfarinmentioning
confidence: 99%
“…At that time, healthy cattle suddenly became dying of internal bleeding and the cause was unknown 11 .Karl Link and his students started the isolation of the active substance from the coumarin that caused the bleeding and found 3,3'methylene-bis-[4-hydroxycoumarin], naturally oxidized coumarin was found in hay fed to livestock 12 . The bleeding disease is also known as -sweet clover disease‖ because livestock eat sweet clover that has been infected with the fungus 13. In research, it was found that natural coumarin is oxidized in moldy hay, to form a substance better known as dicoumarol 13 . The discovery of the bioactive properties of dicoumarol resulted from the investigation of a mysterious livestock disease in the 1940s and later developed as a drug in the 1950s as warfarin 14. Warfarin was first used in 1948 as a rodenticide before the US Food and Drug Administration (FDA) approved it for medical use for anticoagulants in 1954.…”
Section: Overview Of Warfarinmentioning
confidence: 99%